The influence of "Cooperative learning" on academic achievement by technical English students at USB, Coast branch campus - Meza, Marina; Pérez, Edith (Íkala, Revista de Lenguaje y Cultura, 2001)
In general, students of applied sciences who take courses in technical English perform poorly. Hence the relevance of cooperative learning as a teaching strategy which might serve to tackle this problem. In the following article, the authors describe the methodology, development and results of their research into this strategy. How to reference this article: Pérez, E. (2001). Influencia del uso del "aprendizaje cooperativo" en el rendimiento académico de los estudiantes de inglés técnico de la usb, sede del litoral. Íkala. 6(1-2), pp. 31 – 41